Picosecond all-optical switching and dark pulse generation in a fibre-optic network using a plasmonic metamaterial absorber - Xomalis, Angelos (2019)
Coherent interaction of two light waves on a film of subwavelength thickness provides remarkable opportunities for controlling intensity and polarization of light beams as well as all-optical image processing. Here, we show that such interactions can be used for optical dark pulse generation and basic all-optical signal processing in fully fiberized coherent information networks with 1 THz bandwidth. With an encapsulated plasmonic metamaterial absorber operating in the telecommunications C-band, we demonstrate switching and dark pulse generation with 1 ps laser pulses.